2021
DOI: 10.1080/20445911.2021.1994980
|View full text |Cite
|
Sign up to set email alerts
|

The effect of different delivery modes of misinformation on false memories in adolescents and adults

Abstract: The current study examined the effects of different delivery modes of misinformation on false memory creation in adolescents and adults. Forty adolescents (14-15 year olds) and fifty-three adults (over 18) were instructed to watch a video. Following this, half of the participants were given direct-with interaction misinformation, in which misinformation was delivered by the experimenter and participants (co-witnesses) were able to interact before their memory was tested. The other half of the participants were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…These developmental changes could affect the eyewitness performance among adolescents, for example reporting less details than adults (Jack et al, 2014;Pozzulo et al, 2013;Sheahan et al, 2017). However, Irwanda et al (2022) found that there was no statistical difference in true memory of adolescents and young adults. Their study also found that adolescents were more susceptible to misinformation and produced more false memories than young adults.…”
Section: Age and The Cognitive Interviewmentioning
confidence: 93%
See 2 more Smart Citations
“…These developmental changes could affect the eyewitness performance among adolescents, for example reporting less details than adults (Jack et al, 2014;Pozzulo et al, 2013;Sheahan et al, 2017). However, Irwanda et al (2022) found that there was no statistical difference in true memory of adolescents and young adults. Their study also found that adolescents were more susceptible to misinformation and produced more false memories than young adults.…”
Section: Age and The Cognitive Interviewmentioning
confidence: 93%
“…However, Irwanda et al (2022) found that there was no statistical difference in true memory of adolescents and young adults. Their study also found that adolescents were more susceptible to misinformation and produced more false memories than young adults.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Importantly, people may outwardly agree with others while knowing perfectly well that they do not actually agree (i.e., “compliance”; Gudjonsson, 2013) or because they have incorporated the suggested information into their own memory (i.e., false memory). Research on false memories implanted by suggestion has overwhelmingly been conducted with participants from WEIRD countries, with a few exceptions in Indonesian (Irwanda et al, 2022; Maulina et al, 2021) and Chinese (Zhu et al, 2010) samples. We are aware of only two studies that examined cross-cultural differences in false memory formation.…”
Section: Misattribution and Suggestibilitymentioning
confidence: 99%